Commodification of Culture Transgresses Religious Boundaries. - Mehta, Shalina (2009)
Our obsession with religiosity and ethnicity has clouded our vision to record the significance of many silent revolutions that are transgressing boundaries assumed to be impermeable. Visual media and in particular techno revolution brought by cable television has achieved what primordial thinking would reason is impossible. Formation of what are described as electronic communities has created ruptures in the domains of presumably pristine cultures creating disjuncture in symbolic and significant rituals and cultural practices. It also at the same time creates linkages that cross-cut borders created by nation, religion, territory and class. This article documents an empirical study using qualitative methods of research that shows how popular serials have brought in cultural transformations among a section of Muslim women living in an urban slum in Delhi. Given this as representative of a larger change that may be result of commodification of culture, the fusion has important implications for the future understanding of transnational connections..